Analisis Kesulitan Siswa SMP Dalam Menyelesaikan Soal Geometri Bangun Ruang Sisi Datar - Parindang, Edwin Amanu; Yuspelto, Nabil Maulana; Ramlan, Wahyudi; Angraini, Lilis Marina (EDUPEDIA Publisher, 2024)
This study aims to analyze the difficulties students face in solving geometry problems related to polyhedral shapes. The indicators used in this study are competency achievement indicators. The research method employed is descriptive with a quantitative approach. Data collection techniques involved administering essay tests to students, followed by correction and analysis of their answers. The research was conducted at SMP Negeri 1 Tualang with eighth-grade students during the second semester of the 2023/2024 academic year. The study population consisted of eighth-grade students, with a sample of 25 students. The researcher used an essay test as an instrument to gather data. The test results were analyzed by measuring the percentage of each indicator. The test instrument comprised five essay questions. The results showed that students at the school still experience difficulties in solving problems related to polyhedral shapes.